Electrode-Tip Configuration Effects on Weld Quality of RSW of HSLA 340 Steel Sheets: Numerical and Experimental Study - Gillela P.K.R.; Kishore K.; Jaidi J.; Manogna K.G.; Kannan R. (My University, 2025)
This work presents coupled simulations and experimental study to unravel the effect of electrode-tip configurations on the evolution of current density, weld nugget size, thermal, dynamic resistance and associated changes in hardness and joint strength. A 2-D axisymmetric electro-thermomechanical coupled model was developed using COMSOL Multiphysics software and applied for the resistance spot welding (RSW) of high-strength low-alloy steel sheets. Simulation results revealed that the electrode-tip configuration significantly influenced the current density distribution, thermal profiles and dynamic resistance. It was found that the microstructures in weld nugget zone and upper critical heat-affected zone were predominantly martensite with all three electrode-tip configurations because of high cooling rates inherently present in RSW process and reasonable hardenability of the studied steel. However, the electrode-tip configuration showed a significant effect on the weld nugget size due to the variation in current density at the interfaces. The predicted dynamic resistance curve demonstrated that nugget initiation and growth rates were slower with a truncated electrode tip. A good agreement (4-7% error) was achieved between the measured and predicted nugget diameters and approximate areas. Therefore, the authors recommend using a radius electrode tip to maximize the joint strength (nugget size) and failure energy and minimize the electrode indentation depth. Furthermore, the microstructure/hardness across the weldment was established based on the estimation of geometrically necessary dislocation (GND) density. © ASM International 2025.